STUDI PERENCANAAN ALTERNATIF GEDUNG LABORATORIUM TERPADU DENGAN METODE KOMPOSIT UNIVERSITAS JEMBER - Dendi Sephanie; Warsito Warsito; Bambang Suprapto (Universitas Islam Malang, 2020)
Planning on buildings with many floors requires the structure of the building to be safe and avoid the failure of structures that can cause financial and psychological losses. Oneof the most important stages of structural planning is the selection of implementationmethods and materials on the structure itself, in this case the focus on this research is analternative study for buildings with many floor numbers. The integrated laboratorybuilding of the University of Jember has a floor of 7 floors with concrete structure. Themethod used in this research is an alternative method of using a composite structure,which utilizes the strength of steel in terms of carrying the burden of working andutilizing the fire-resistant, concrete properties that are easily obtained. The initial stageof the study was to plan a thick floor plate that corresponds to the load and obtained athick 130 mm floor plate then continued to plan the last beam and column was theFoundation planning to assume the building and load working on the building. The finalresult of the study gained the use of the WF profile steel 300.300.10.15 in the column andWF 700.300.13.24 the parent beam, WF 350.175.7.11 the beam which between thecolumns and the beam using a semi-rigidconnection, on the child and mains beamconnection using a simple connection connection while the foundation uses bore pile witha depth of 20 meters.Keyword: Composite Structure, WF Profile, Bore Pile Foundation